Peran Teknis Dan Psikososial Mentor Dalam Mentoring Kewirausahaan Bagi Mahasiswa Pendidikan Luar Sekolah Universitas Palangka Raya: The Technical and Psychosocial Role of Mentors in Entrepreneurship Mentoring for Out-of-School Education Students at Palangka Raya University - Saifullah Darlan; Ade Yusuf Ferudyn; Yesni Nopy; Kusnida Indrajaya; Ruth D.R. Silalahi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
College graduates still contribute significantly to Indonesia's open unemployment rate. Providing materials on entrepreneurship can help students to provide job opportunities and build their businesses. This study seeks to determine the technical and psychosocial roles from mentors in the cultivation phase adopted from Kram to be applied in entrepreneurship mentoring for PLS students. This research uses a qualitative method with a comparative descriptive approach. Determination of subjects using purposive sampling. Data were collected using observation, skill testing, and structured interviews. The research results shows that the technical role of the mentor appears in the process of exposure and review of business plans. Mentors confirmed that students technical understanding was in a good position in terms of originality and innovation in their product design, business planning and detailed financial management. This was reflected by the results of the skill test with an average score of 73.1/100. Mentors are considered by students to have carried out their psychosocial role because of the ability to provide motivation and understanding of entrepreneurship. This role encourages students to feel more confident, have strong intentions, dare to move forward, dare to accept criticism, dare to take risks, willingness to learn and adapt, consistency, and not giving up on their business. As a follow-up, facilitation was conducted by the mentors to improve the students' business plans.